KAJIAN INDEKS DAYA SAING DESA/KELURAHAN DI PROVINSI JAWA TENGAH - Bimo Aji Dimas Danindro; Harmawanti Marhaeny (Universitas Tidar, 2020)
Village development positions the village as a subject of development that must be able to manage its own development. Competitiveness that is interpreted as the ability to achieve the absolute development goals must also be owned by the village to realize an effective village development policy. The limited competitiveness measure up to the village level shows the urgency of the establishment of these indicators. Related to this problem, this research forms a village-level competitiveness index and its comparability to kelurahans so that an evaluation of existing policies can be carried out as a whole. The composite index formed refers to the method developed by the Organization of Economics Co-operation and Development (OECD). This index covers 5 dimensions and uses 2014 Village Potential data (PODES). This study produces a composite index of village competitiveness that is quite relevant seen from the positive and significant correlation values with the Village Development Index. In this study, rural / urban villages are grouped into 3 namely low, medium and high competitiveness. From the results of this study, there is a fact that villages in the highlands tend to be categorized as low competitiveness. In addition, villages with low competitiveness are concentrated in many districts such as Purworejo, Rembang, Wonosobo, Blora, and Wonogiri. In general, the causes of underdeveloped villages that are low in competitiveness are health and economic dimensions which should be a priority for the government's attention.